1996
DOI: 10.1136/thx.51.8.869
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus laryngotracheobronchitis presenting as stridor in a patient with peripheral T cell lymphoma.

Abstract: radiograph and computed tomographic scan were normal. Aspergillus fumigatus was isolated repeatedly from the sputum from day 9 onwards, and blood cultures were negative for bacteria and fungi. Broad spectrum antibiotics and granulocyte colony-stimulating factor were administered. His fever gradually subsided and the white blood cell count increased to 7.2 x 109/l on day 24 with an absolute neutrophil count of 4.5 x 1 09/l. However, the hoarseness and productive cough persisted. The oxygen saturation of haemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…However, the coexistence of various pathological features, such as occlusion, ulceration and pseudomembranes, has often been observed in IATB patients [4,11,19,21,22,26,27,29–33]. There are also reports of some histologically diagnosed IATB patients who showed mild superficial mucosa erosion or necrosis only [4,10,11,18,25,34–36]. In 1993, Kemper et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the coexistence of various pathological features, such as occlusion, ulceration and pseudomembranes, has often been observed in IATB patients [4,11,19,21,22,26,27,29–33]. There are also reports of some histologically diagnosed IATB patients who showed mild superficial mucosa erosion or necrosis only [4,10,11,18,25,34–36]. In 1993, Kemper et al.…”
Section: Discussionmentioning
confidence: 99%
“…DENNING et al [66] found itraconazole to be as effective as amphotericin-B, however, its role needs to be further studied. Itraconazole is also used empirically as a prophylaxis against aspergillus in high-risk patients with neutropenia or on long-term corticosteroid therapy [67][68][69][70][71].…”
Section: Diagnosis Of Invasive Aspergillosismentioning
confidence: 99%
“…In pediatric patients with invasive aspergillosis, having undergone HCT led to a sixfold higher risk of death and the only predictor of improved survival was surgical intervention [20]. Survival of AT is possible if diagnosis is made promptly and provided the patient can tolerate removal of the infected material [5, 15, 16, 18, 21]. …”
Section: Discussionmentioning
confidence: 99%